Detection of Conflicts and Inconsistencies in Taxonomy-based Authorization Policies - Mohan, Apurva (2011)
The values of data elements stored in biomedical databases often draw from biomedical ontologies. Authorization rules can be defined on these ontologies to control access to sensitive and private data elements in such databases. Authorization rules may be specified by different authorities at different times for various purposes. Since such policy rules can conflict with each other, access to sensitive information may inadvertently be allowed. Another problem in biomedical data protection is inference attacks, in which a user who has legitimate access to some data elements is able to infer information related to other data elements. We propose and evaluate two strategies; one for detecting policy inconsistencies to avoid potential inference attacks and the other for detecting policy conflicts.